Turning evidence into action: The role of research in shaping policy - Akbar, M Agung (Indonesian Journal of Health Services, 2024)
Evidence-based policy is essential for addressing complex global challenges such as health crises, climate change, and social inequalities. Despite its importance, translating research findings into effective public policy remains difficult due to gaps between researchers and policy makers, including differences in language, priorities, and working approaches. Strengthening communication and collaboration between academia and government is necessary to ensure that scientific evidence can inform policy decisions. Institutional mechanisms, adequate funding, and research agendas aligned with societal needs are also crucial to support evidence-based decision making. Strong synergy between research and policy will enable governments to develop more responsive, effective, and sustainable public policies.